Efeito de cinco dias de acampamento de férias e três meses de acompanhamento sobre fatores de risco cardiovascular e estilo de vida em crianças com sobrepeso e obesidade - Rauber, Suliane Beatriz (2016)
Sedentary behavior, coupled with poor diet has increasingly reached children, teenagers and their families worldwide. The drastic reduction in the time devoted to active and spontaneous movement has been a matter of great concern among professionals who are dedicated to the prevention of diseases in children and adolescents, since the sedentary lifestyle has contributed to the increasing incidence of obesity and chronic diseases such as hypertension. Educational programs have been considered an important tool to improve this situation. The objective of the study was evaluate the impacts of a Recreational Education Program in Children’s Health (PRESI) through a camp, weekly meetings and by the use of an application on metabolic control, cardiovascular responses, physical fitness, level of knowledge about healthy habits, lifestyle changes of children with overweight and obesity. The PRESI was divided into Phase 1 involved a five-day summer camp called ACAMP, and PHASE 2 comprised 12 weeks of follow-up with a weekly meeting totaling 12 meetings of two hours each (12 weeks). ACAMP participated in 20 children (9 boys and 11 girls; 9.4 ± 1.1 years), and of these 20 children, 12 (9.4 ± 0.96 years) also participated in the follow-up during 12 weeks. Anthropometric, blood pressure and resting heart rate were measured in addition to the completion of the thermal stress test Cold Pressor Test, blood collections for evaluating biochemical variables (glucose, lipemia and apolipoproteins A-1 and B), level of physical activity , food intake, sleep quality and level of knowledge about health. For pre and post camp comparison we used the Student t test (t) and three times (pre and post ACAMP and 12 weeks), with normal distribution, it used ANOVA for repeated measures. We use the test d'Cohen to verify the magnitude of the responses by the sample is small. For comparison of food proportions between groups, we used the McNemar test. Was adopted p <0.05 for statistically significant differences. Results Phase 1: Significant reduction in SBP (115.15 ± 10.40 vs 105.80 ± 8,58mmHg) and DBP (77.10 ± 9.26 vs 70.00 ± 6,49mmHg) was observed when pre- vs. post ACAMP were compared respectively (p <0.05). When comparing pre and post ACAMP observed that: HOMA beta showed a decrease of 56.2% (98.8); lipid profile was decreased CT 18.95 mg / dl, LDL 9,7mg/dL, non-HDL 16.15 mg/dL and triglycerides 27.05 mg / dl; and APO A1 and B had an average decrease of 8% (- 10.3 mg / dl) and 9% (- 7.6 mg/dL), respectively. Phase 2: the resting PAS reduced 8,92mmHg and 6,58mmHg and 1,67mmHg 2 mmHg and DBP after ACAMP and 12 weeks, respectively, when compared with the pre times. The average basal insulin fell 5.59 μUI / ml after ACAMP compared with the pre and these values remained low after 12 weeks. CT decreased 13.4% after ACAMP (p <0.003) and 18.9% after 12 weeks and APO A1 fell by 9,42mg / dl post ACAMP (p = 0.31) and 4,42mg / dl (p = 0.59) after 12 weeks compared with pre. The total NAF increased (16.95%, 172.99 METs) and among the types of households that had higher increases the Leisure is what has improved significantly, both during the week (NAFLDS increase of 26.06%, p <0.001) as the weekend (NAFLFS increase of 14.1%, p <0.001). Hear drop in sedentary time during the week of 1585.71 ± 208.58 to 1408.57 ± 174,10min (p = 0.004) and at the end of the week time decreased from 282.14 ± 41.23 to 240.71 ± 36,17min (p <0.001). The score of sleep quality decreased after 12sem (58.46 ± 4.87 to 50.52 ± 4.63, p = 0.074) and the level of knowledge about health education compared to pre increased 16.7% post ACAMP and 19.12% after 12 weeks (p<0,05). We conclude that five days in a camp and 12 health education meetings, with physical activity and encouraging healthy lifestyle contributed to reducing and maintaining body mass, reduction of cardiovascular risk factors such as high blood pressure at rest, CT, triglycerides. Improves the lifestyle of children, an increase NAF and decreased time devoted to sedentary activities, improves sleep quality and choice for healthier foods.